Money Politics in Indonesian Regional Election Disputes: Constitutional Court Reasoning and Electoral Integrity - Diar, Adithiya; Zarkasi, A; Sayuti, Sayuti; Abd Aziz, Saidatul Nadia; Antasari, Rr. Rina (Faculty of Law, Jambi University, 2026)
This article examines how the Constitutional Court assesses and interprets money politics in dispute cases over regional head election results in Indonesia and what this court settlement means for electoral integrity. It addresses three dispute cases concerning vote-buying allegations in regional elections, corruption of voter choice, violations of constitutionally mandated electoral processes, and examines the effect of money politics on the legitimacy of revoting. As normative legal research, this article analyses how the Court formulates its legal reasoning, applies standards of proof, and evaluates the relationship between electoral violations and final results. It is learnt that the Court has developed a relatively consistent reasoning model. The Court initially determines whether sufficiently convincing facts support a finding of vote buying, examines whether the violation has tainted the purity of voter choice, and subsequently assesses whether the violation has had a significant effect on the election outcome. This article further demonstrates that money politics is no longer viewed merely as an electoral crime, but as a constitutional issue when it undermines democratic legitimacy and distorts the authenticity of electoral results. Unlike earlier studies that mainly discuss money politics in terms of its forms, causes, or general consequences for local democracy, this article frames jurisprudential consistency as the central analytical problem. It offers a more systematic account of how the Court connects proof, voter autonomy, and electoral impact. It argues that clearer more predictable standards are needed to strengthen legal certainty, improve the adjudication of election disputes, and reinforce protections for electoral integrity in Indonesia